The Effect of Antimicrobial Photodynamic Therapy with Radachlorin and Toluidine Blue on Streptococcus Mutans: An in Vitro Study - S. Vahabi; R. Fekrazad; S. Ayremlou; S. Taheri; N. Zangeneh (Tehran University of Medical Sciences, 2011)
Objectives: Dental caries and periodontal diseases are caused by infection of teeth and supporting tissues due to complex aggregate of bacteria known as biofilm, firstly colonized by streptococci. The main purpose of this in vitro study was to evaluate the antimicrobial effects of toluidine blue O (TBO) and Radachlorin® in combination with a diode laser on the viability of Streptococcus mutans. Materials and Methods: Bacterial suspensions of Streptococcus mutans were exposed to either 0.1% TBO associated with (20 mW, 633 nm diode laser, continuous mode, 150 s) or 0.1% Radachlorin® and laser irradiation (100 mW, 662 nm diode laser, continuous mode, 120 s). Those in control groups were subjected to laser irradiation alone or TBO/Radachlorin® alone or received neither TBO/Radachlorin® nor laser exposure. The suspensions were then spread over specific agar plates and incubated aerobically at 37°C. Finally, the bactericidal effects were evaluated based on colony formation. Results: Potential bacterial cell killing was only observed following photosensitization with TBO and 3 j/cm2 laser exposure (p<0.05), whereas Radachlorin® showed significant reduction in dark condition compared to laser exposure (p<0.05). Conclusion: TBO-mediated photodynamic therapy seems to be more efficient than Radachlorin ® in significantly reducing the viability of Streptococcus mutans in vitro.